BETWEEN TRUST AND THE LAW: ETHICS AND ETHICAL CHALLENGES IN THE WORK OF THE CRIMINAL PSYCHOLOGIST - Zaimova-Tsaneva, Emelina Valentinova (Psychological thought, 2025)
This paper shows the key ethical principles in the professional practice of criminal psychologists. The analysis is structured around the five core principles outlined in the Ethical Principles of Psychologists and Code of Conduct of the American Psychological Association: beneficence and nonmaleficence, fidelity and responsibility, integrity, justice, and respect for people’s rights and dignity. Specific ethical challenges such as confidentiality, informed consent, dual loyalty, and maintaining professional competence are addressed.. References to the Bulgarian ethical and legal framework are also included. The aim is to delineate the boundaries of ethically responsible conduct in conditions of heightened legal, institutional, and moral complexity. The analysis emphasizes the significance of a high level of ethical awareness, self-reflection, and ongoing professional development in maintaining justice, human dignity, and professional legitimacy in the practice of criminal psychology.